Syaikh Abdul Malik: Biografi dan Perannya terhadap Masyarakat di Desa Kedung Paruk Kecamatan Kembaran Kabupaten Banyumas (1881-1980 M) - Hafsah Munawaroh (Progam Studi Sejarah Peradaban Islam (SPI), Fakultas Ushuluddin Adab dan Humaniora, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study aimed to determine the biography and role of Syaikh Abdul Malik towards the community in Kedung Paruk Village, Banyumas Regency (1881-1980M). The method used in this study was a historical research method consisting of heuristics or data collection, source verification or criticism, interpretation or sorting of sources, and historiography or historical writing. The sources used were library research and interview techniques. At the same time, this study used a biographical approach to find out how the life history of Syaikh Abdul Malik. In this study, the theory used was the role theory. The results of this study discussed the biography of Syaikh Abdul Malik starting from his family background, family tree, educational history, and the environment when he was still alive in the community in Kedung Paruk Village. The role of Syaikh Abdul Malik towards the community in Kedung Paruk Village was by establishing the Bani Malik Islamic Boarding School which is used as a place to carry out religious activities with his family and the local community. Syaikh Abdul Malik also adhered to the Tarekat Nasaqsyabandiyah Khalidiyah which was developed in Kedung Paruk Village. In the spread of Islam among his people, Syaikh Abdul Malik harmonized the teachings of the tarekat with the shari'a.